A Production systems study of J.A. Castillo and Company. Incorporated - Luna, Baby Helen A. (Diliman, Quezon City College of Engineering, 1991)
J.A. Castillo and Company, Incorporated (JACCI) is a manufacturer of re-embroidered lace used as materials for bridal gowns, curtains or table cloths. The plantsite os located at As-is, Bauan, Batangas on a 9200 square meter lot. The company started in 1978 and it has been operating for 13 years now. They have a total of 985 workers in the plant site and about 700 sewing machines. JACCI is strictly subcontracting from Barbizon, Philippines, Incorporated (BPI)_ which is a branch of Barbizon U.S.A. All the raw materials are imported from the U.S.A. office except the thread which is bought here in the Philippines. Therefore, JACCI basically offers labor to the Barbizon company. Job orders from the U.S.A. are given to the BPI. BPI then arranges these orders to be given to provincial subcontractors such as JACCI. The materials from abroad takes two weeks to one month to be shipped to the Philippines. The job orders are then worked on only after that period. This project's objective is to use the principles of Production and Operations Management to eliminate problems in delays of raw material delivery, which is a constant problem of the firm. This affects both the company in the sense that it has some idle equipment when there are work stoppages, and the workers in the sense that since payment is by piecework, they do not receive wages when there is no available work. The study will also propose measures on how the make use of the idle time of the machinery. Thus, the capacity of the company is used to the fullest., which will result to greater efficiency for the advantage of both the company and the workers.
IE 151
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: J.A. Castillo and Company, Incorporated; Manufacturing industry; Production engineering